Anatomical and molecular characteristics of Limnophila rugosa (Roth) Merr. - Le, Hong Thia; Huynh, Nguyen Tuong An; Thuy, Vo Thi Thu; Ngo, Ngoc Hung; Le-thi, Thu Trang (Journal of Phytology, 2025)
Limnophila rugosa is a perennial plant and has been used as a medicinal and agricultural plant in some Asian countries. In this study, we provided the ITS and trnL-F regions and the anatomical characteristics of L. rugosa for the first time. Based on these molecular regions, phylogenetic trees showing relationships between L. rugosa and other species belonging to the Scrophulariaceae and Plantaginaceae families were performed and the result showed that L. rugosa was nested within the family Plantaginaceae instead of Scrophulariaceae. Additionally, the details of the micro-morphological characteristics of L. rugosa were investigated for the first time.